Primary gastric choriocarcinoma: A case report - Zhang, Xusheng; Yan, Yuke; Meng, Yun; GUO, Huijun; PENG, Jiangshan; DU, Xunqin; Yang, Xiaojun (Frontiers in Surgery, 2022)
Choriocarcinoma is a malignant tumor originating from the trophoblast. Most are gestational choriocarcinomas, which usually occur in women of placental chorionic epithelial origin and are associated with pregnancy. They mainly originate from the gonads such as the ovaries and testes, and rarely occur in the stomach. Very few of these are choriocarcinomas not related to pregnancy, also known as primary choriocarcinomas. Primary gastric choriocarcinoma (PGC) is extremely rare.